Who Should Own the League? Transaction Costs and the Structure of NBA Ownership. (January 2022) - Nonnenmacher, Tomas; Gerard, David
Like many professional sports leagues worldwide, the National Basketball Association is organized as a cooperative of team owners. We argue that league ownership structures must balance two types of transaction costs: the costs to league owners of collective decision-making and the costs of contracting with stakeholders of the league, importantly players, owners, and potential investors. We compare the transaction costs of the current team owned league with the alternatives of investor and player owned leagues, finding that each ownership structure reduces some transaction costs while raising others.